CORRELATION OF ALBIAN RADIOLARIAN ASSEMBLAGES FROM THE GREATER CAUCASUS, EUROPE, AND MEDITERRANEAN - Kazintsova L.I. (My University, 2002)
Generalized data on Albian radiolarians from the Greater Caucasus refine composition of their Spongostichomitra elatica (middle Albian) and Dictyomitra disparlita-Crolanium triangulare (upper Albian) assemblages. The assemblages are correlated with coeval (or close in age) radiolarian faunas of the Crimea, Russian platform, Poland, Czechoslovakia, Romania, Yugoslavia, Italy, Spain, and Tunisia. The correlation revealed many species in common. These species suggest that above regional basins were interconnected and offer a possibility for a broad correlation of late Albian-Cenomanian deposits of the Greater Caucasus, Crimea, Russian Platform, and Mediterranean region. Late Albian radiolarians of the Greater Caucasus are pictured under scanning microscope for the first time.
Keywords: Albian; Mesozoic::Cretaceous::Lower::Albian; Мезозой::Меловая::Нижний::Альбский